2018
DOI: 10.1002/prp2.438
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of the selective GPR120/FFA4 agonist compound A is not effective in alleviating tissue inflammation in mouse models of prototypical autoimmune diseases

Abstract: Abstractω3‐polyunsaturated free fatty acids (ω3‐PUFAs), particularly docosahexaenoic (DHA) and eicosapentaenoic acid (EPA), are thought to exert health promoting effects in metabolic and in inflammatory diseases. The molecular mechanisms of these beneficial effects are only partially understood. DHA and EPA activate Free Fatty Acid receptor 4 (GPR120/FFA4). Recently, the first orally available, synthetic ligand of FFA4, 3‐[2‐chloro‐5‐(trifluoromethoxy)phenyl]‐3‐azaspiro[5.5]undecane‐9‐acetic acid (“compound A”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
13
2
Order By: Relevance
“…On the other hand, Wannick et al reported that oral administration of 50 mg/kg compound A was not effective in alleviating tissue inflammation in mouse models of autoimmune diseases, specifically imiquimod-induced psoriasis-like dermatitis, K/BxN serum transfer arthritis, and antibody transfer pemphigoid disease-like dermatitis; the dosage of compound A used in this study was even higher than that used in our study (30 mg/kg) [ 33 ]. There are three different factors to consider when comparing the two studies.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, Wannick et al reported that oral administration of 50 mg/kg compound A was not effective in alleviating tissue inflammation in mouse models of autoimmune diseases, specifically imiquimod-induced psoriasis-like dermatitis, K/BxN serum transfer arthritis, and antibody transfer pemphigoid disease-like dermatitis; the dosage of compound A used in this study was even higher than that used in our study (30 mg/kg) [ 33 ]. There are three different factors to consider when comparing the two studies.…”
Section: Discussioncontrasting
confidence: 71%
“…Because compound A was effective against insulin resistance and adipose tissue inflammation in C57BL6 mice when administered orally [ 15 ], two factors could not explain the negative outcomes of the autoimmune disease models used by Wannick et al Further investigation is necessary to elucidate why compound A was not effective against autoimmune diseases. Wannick et al suggested that FFA4 activation does not significantly contribute to the health-promoting effects of omega-3 polyunsaturated fatty acids in autoimmune diseases [ 33 ]. This possibility could be partly supported by the specialized proresolving mediators of DHA and EPA derivatives, such as resolvin D1, resolvin D2, resolvin E, protectin D1, and maresin 1 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purified anti-Col7 IgG were filter-sterilized (pore size 0.2 μm), quantified by NanoDrop (Thermo Fischer Scientific GmbH, Dreieich, Germany), and assessed for their reactivity to murine Col7 by indirect immunofluorescence analysis performed on murine tail skin sections as previously described ( 21 ). Antibody transfer BP-like EBA was induced, as previously described ( 12 , 21 ). Briefly, mice were injected s.c. with 50 μg of affinity purified anti-Col7 IgG on days 0, 2, and 4 of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies have suggested that therapies based only on FFA4 receptor activation would not be helpful in the treatment of inflammatory diseases. They observed that Compound A did not modify the course of Aldara-induced psoriasis-like dermatitis, K/BxN serum transfer arthritis, or antibody transfer pemphigoid disease-like dermatitis (Wannick et al, 2018 ). Metabolex 36 and metabolex compound B have been used as FFA4 receptor agonists.…”
Section: Long-chain Fatty Acid Receptors In Immune Cellsmentioning
confidence: 99%